NRC4 Gene Cluster Is Not Essential for Bacterial Flagellin-Triggered Immunity. Issue 1 (11th November 2019) - Wu, Chih-Hang; Adachi, Hiroaki; De la Concepcion, Juan Carlos; Castells-Graells, Roger; Nekrasov, Vladimir; Kamoun, Sophien
Abstract : CRISPR/Cas9-mediated mutation of NRC2, NRC3, and NRC4 genes did not affect bacterial flagellin-triggered immunity.